Measurement of natural radioactivity in soil dust samples along roadways in high commercial areas of the Ketu South district of the Volta Region, Ghana - Moses Ankamah Addo; Jonathan Sowatei Lomotey; Bernard Osei; Kwame Appiah (Radiation Protection and Environment, 2020)
There are increasing awareness and concern about the radiological impact of dust from soils along the roadways on petty traders and commuters in major commercial areas of Ghana. Soils in such commercial areas can be contaminated by road dust that could alter their radiological characteristics. This is because of the general exposure of road dust to environmental elements such as industrial and urban activities and also exhaust fumes from the vehicles. In the present study, 52 surface soil samples were collected along six roadways in the Ketu South District of the Volta Region, Ghana. The study area is one of the high commercial activities and consequently high traffic density. The measures of the specific activity concentration of238U,232Th, and40K in the samples were taken using high-purity germanium (HPGe) gamma-ray spectrometry. The results were evaluated to assess the radiological impact due to roadside soil in the area. The activity concentration in the samples ranged from 74.62 to 156.3 Bq/kg for238U, with an average of 112.4 Bq/kg. The activity concentrations of232Th ranged from 6.5 to 29.0 Bq/kg, with an average of 14.6 Bq/kg and that of40K ranged from 83.76 to 224.27 Bq/kg with an average of 141.02 Bq/kg. The results were used to estimate the radiological parameters of the study soils. The levels of radium equivalent activity (Raeq), absorbed dose rate (D), and annual effective dose (E) in them were lower than the recommended or safe limits proposed by international bodies such as UNSCEAR (2000) or ICRP (1991). These findings indicated that soils in the studied area had the normal levels of radiation and were therefore radiologically safe.